Penerapan Media Audiovisual dalam Meningkatkan Keterampilan Menyimak Dongeng Siswa Kelas III MIS Darul Ulum Muhammadiyah Bulukumba - M. Nur Hakim (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
The aims of study was to explain the process and implementation results of audiovisual media in improving fairy tales listening of third grade MIS Darul Ulum Muhammadiyah Bulukumba students. The research was action research for 2 cycles, which included planning, implementation, observation, and reflection. The obtained research data were observation, field notes, and tests, while the data were analyzed by qualitative and quantitative method. The results of observations and field notes were analyzed qualitatively, while, the results data of tests of each cycle were analyzed quantitatively. Data wetness test using triangulation. The results of the data analysis revealed that: 1. during the process of implementing audio visual media was increase in listening to fairy tales skills, it was seen in students' ability to identify the contents of the story, such as themes, characterizations, plot, setting, and mandate, and 2. improvement results seen in students learning completeness that in the first cycle the average score was only 61.75, increasing to 76.25. These results concluded that audiovisual media have a positive impact in improving fairy tales listening skill of third grade MIS Darul Ulum Muhammadiyah Bulukumba students.